Recurrence of Postpartum Hemorrhage in Relatives: A Population-based Cohort Study. Issue 4 (21st December 2022) - Linde, L.E.; Ebbing, C.; Moster, D.; Kessler, J.; Baghestan, E.; Gissler, M.; Rasmussen, S.
Abstract : ( Acta Obstet Gynecol Scand . 2021;100:2278–2284. doi: 10.1111/aogs.14262) While postpartum hemorrhage (PPH) continues to be a serious cause of maternal mortality and morbidity worldwide, there are very few studies on the family aggregation of PPH, and existing studies give inconsistent results. Impact of current birthweight on PPH recurrence between relatives has also not been studied. The aim of this study was to determine PPH recurrence in relatives, the impact of birthweight on PPH recurrence, and the rate at which family history of high birthweight and PPH contributes to current PPH cases.